A randomised, double‐blind, trial of the safety and efficacy of omarigliptin (a once‐weekly DPP‐4 inhibitor) in subjects with type 2 diabetes and renal impairment. Issue 6 (27th April 2017) - Chacra, Antonio; Gantz, Ira; Mendizabal, Geraldine; Durlach, Lucila; O'Neill, Edward A.; Zimmer, Zachary; Suryawanshi, Shailaja; Engel, Samuel S.; Lai, Eseng
Summary: Aims: To assess the safety and efficacy of omarigliptin in subjects with type 2 diabetes mellitus (T2DM) and chronic renal impairment (RI). Methods: Patients with T2DM with moderate RI (estimated glomerular filtration rate [eGFR] ≥30 to <60 mL/min/1.73 m 2 ) (N=114), severe RI (eGFR <30 mL/min/1.73 m 2 ) (N=55) or end‐stage renal disease on dialysis (N=44), who were either not on an antihyperglycaemic agent therapy for at least 12 weeks at screening, washed‐off of oral antihyperglycaemic agent monotherapy or low‐dose dual combination therapy, or on insulin monotherapy, with baseline glycated haemoglobin (HbA1c) of 6.5%‐10.0% were randomised to omarigliptin or to placebo for 24 weeks (primary end‐point) followed by a 30‐week period with subjects on placebo switched to blinded glipizide (if not on insulin). Results: After 24 weeks, from a mean baseline HbA1c of 8.4% in the omarigliptin group and 8.3% in the placebo group, the least squares mean (95% CI) change from baseline in HbA1c in the overall population (all renal strata combined) was −0.77% (−1.00 to −0.54) in the omarigliptin group and −0.44% (−0.67 to −0.21) in the placebo group; between‐group difference of −0.33% (−0.63 to −0.02); P =0.035. After 24 weeks, the incidences of subjects with symptomatic hypoglycaemia, one or more adverse event (AE), drug‐related AE, serious AE and discontinuation due to an AE were similar in the omarigliptin and placebo groups. Conclusions: In this study in subjects with T2DM and RI, relative to placebo, omarigliptin provided clinically meaningful reductions in HbA1c, had a similar incidence of symptomatic hypoglycaemia and was generally well tolerated.